A customized construction method for a bimodal structure of a high-strength and high-toughness titanium-based composite material
By customizing the bimodal structure of titanium-based composite materials, regulating their grain size and distribution, the problem of poor inversion relationship between existing titanium-based composite materials is solved, high strength and good plasticity of the material are achieved, and the potential for its engineering application is expanded.
Patent Information
- Application Number
- CN202211623289.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-16
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-12-16
AI Technical Summary
After the introduction of the reinforcement, the strong-plastic inversion relationship of existing titanium-based composite materials is poor, resulting in difficulty in deformation processing, high preparation cost and low use safety, which limits the expansion of their practical applications.
By customizing the grain sizes of coarse and fine crystal regions, adjust the grain size of the raw material powder, assemble powders of different grain sizes, and consolidate at high temperature to form bulk materials to obtain a titanium-based composite material with a bimodal structure.
Without losing plasticity, the strength of titanium-based composite materials has been significantly improved, with a strength of 20% to 35%, and the high strength and toughness matching of the material has been achieved.
Smart Images

Figure CN116037931B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal-based composite materials, and in particular to a method for customizing the structure of a double peak of a high-strength and high-toughness titanium-based composite material. Background Art
[0002] Particle-reinforced titanium-based composites have the properties of light weight, high strength, high temperature resistance, and corrosion resistance, and have been widely used in the fields of aviation, aerospace, automobiles, mechanical biomedical equipment, etc. However, the introduction of reinforcements greatly reduces the plasticity and toughness of titanium-based composites, leading to problems such as difficulty in deformation processing, high preparation cost, and low safety in use, which seriously restricts the further expansion of its practical application. Therefore, how to improve the strength-plastic inversion relationship of titanium-based composites is a key issue in expanding their engineering applications.
[0003] In recent years, many researchers have proposed the academic idea of heterogeneous metal materials, which helps to overcome the problem of mismatch between strength and toughness of metal materials. The basic connotation is to form two soft and hard regions in the material. The hard region (fine-grained region) ensures the material's work hardening ability, and the soft region (coarse-grained region) gives it enough plasticity to passivate or deflect cracks; at the same time, the strain mismatch at the interface between the soft and hard regions is used to induce geometric dislocations, thereby introducing heterogeneous deformation-induced stress, so that the material can have high strength while ensuring greater ductility.
[0004] Therefore, customized matching of soft and hard zones to form grains of different sizes can effectively exert the advantages of heterogeneous structures, thereby precisely controlling the strength and toughness of materials. Previous studies mostly controlled grain size through heat treatment and thermal processing, but the above methods cannot precisely design the proportion of large and small grains, distribution morphology, and component content in a customized manner, and there is instability in the mechanical properties of the material.
[0005] In response to the above problems, the present invention is guided by improving the matching of strength and toughness, customizes the design of coarse-grained areas and fine-grained areas, accurately controls the grain size of raw material powders, customizes the assembly of powders with different grain sizes, and then forms a block material through high-temperature consolidation. The obtained titanium-based composite material forms a customized bimodal structure, which greatly improves the material strength without losing plasticity. Summary of the invention
[0006] The purpose of the present invention is to provide a customized construction method of a bimodal structure of a high-strength and tough titanium-based composite material in response to the problem that the grains cannot be precisely controlled in the prior art. The high-strength and tough titanium-based composite material with a bimodal structure prepared by the present invention has the following two characteristics: First, the grain size in the composite material can be regulated by precisely controlling the grain size of the raw material powder; Second, the bimodal structure is customized and designed and prepared, and its organizational characteristics are as follows: The microstructure consists of two regions: a coarse-grained region and a fine-grained region. The fine-grained region is composed of a titanium-based composite material with a reinforcement content of 1 to 20 vol.%, and micro / nano multi-component reinforcements are evenly dispersed inside it. The grain size of the entire fine-grained region ranges from 3 to 8 μm, while the coarse-grained region is a matrix titanium alloy with a grain size range of 10 to 100 μm.
[0007] The present invention is achieved through the following technical solutions:
[0008] The present invention provides a customized construction method of a bimodal structure of a high-strength and tough titanium-based composite material, and the specific preparation steps are as follows:
[0009] S1. To improve the matching of strength and plasticity, the grain size of the coarse-grained area and the fine-grained area is customized according to the performance target of high-strength and toughness titanium-based composite materials;
[0010] S2. According to the customized design requirements of the grain size of the coarse / fine grain area, the type of powder and the content of the reinforcing phase are adjusted; wherein, the fine grain area uses titanium-based composite material powder A, which includes matrix alloy A1 and reinforcement A2, and the type and particle size of A are adjusted. The type of A is specifically to adjust the type and content of A1 and A2; the coarse grain area uses titanium alloy powder B, and the type and particle size of powder B are adjusted;
[0011] S3, preparing titanium-based composite material powder A selected for the fine grain region according to the type and content of A2 designed in S2;
[0012] S4. According to the design of S2, the powder A obtained in S3 is screened to obtain powders A with different particle sizes;
[0013] S5. According to the design of S2, the titanium alloy powder B is screened to obtain titanium alloy powders B with different particle sizes;
[0014] S6, drying the titanium-based composite material powder A and the titanium alloy powder B obtained in S4 and S5 respectively;
[0015] S7, mixing the two powders obtained in S6 evenly according to the ratio designed in S2 to obtain a mixed powder;
[0016] S8. The mixed powder obtained in S7 is subjected to a dehydrogenation high-temperature consolidation treatment to obtain a high-strength and tough titanium-based composite material with a bimodal structure and different grain sizes.
[0017] Furthermore, in step S1, the grain size of the fine-grained region is in the range of 3 to 8 μm, and the grain size of the coarse-grained region is in the range of 10 to 100 μm.
[0018] Furthermore, in step S2, the particle size range of the titanium-based composite material powder A includes one of 25-53 μm, 53-75 μm, 75-96 μm, 96-120 μm, 120-150 μm, 150-180 μm, 180-230 μm, and 230-250 μm. The matrix alloy A1 in the titanium-based composite material powder A includes one or more of pure titanium and titanium alloy, and the reinforcement A2 includes TiB, TiC, La2O3, Ti x Si y (x=1-5, y=1-4) one or more of the reinforcements. The volume fraction of the reinforcement A2 in the titanium-based composite material powder A is 1-20%, and the reinforcement size includes nanometer size or micrometer size.
[0019] Furthermore, the base alloy powder B described in step S2 includes pure titanium or titanium alloy, and the particle size range includes one of 25-53 μm, 53-75 μm, 75-96 μm, 96-120 μm, and 120-150 μm.
[0020] Further, in step S3, the preparation of titanium-based composite powder A is specifically as follows: the matrix A1 and the reinforcement A2 or the additive for generating the reinforcement A2 are pressed to form an electrode rod, and a titanium-based composite intermediate ingot with uniform composition and standard composite electrode size is prepared by vacuum consumable melting or induction melting technology, and processed into the electrode rod required for powder making, and finally the rod is powdered to obtain a titanium-based composite powder A with an expected reinforcement content; the powder making method includes a rotating electrode method, a water atomization method, and a gas atomization method, preferably an electrode induction melting gas atomization method. Reinforcement A2 refers to a directly added reinforcement (including one or more of TiB, TiC, and La2O3) or an additive (including one or more of B4C, TiB2, LaB6, and SiC), and the additive is added as a reactant. For example, when B4C is added, it reacts with the titanium alloy matrix to generate two reinforcements, TiB and TiC.
[0021] Furthermore, the powder screening described in steps S4 and S5 includes but is not limited to using all equipment and methods that can screen powder, such as a vibration screening machine.
[0022] Furthermore, the powder drying described in step S6 includes but is not limited to using a vacuum drying oven, etc.
[0023] Furthermore, in step S6, in the mixed powder of powder A and powder B, the volume fraction of titanium-based composite material powder A is 10% to 90%.
[0024] Furthermore, in step S7, the mixing method includes ball milling, the speed range of the equipment is 100-400 r / min, the time is 0.5-12 h, and the ball-to-material ratio is 0:1-5:1. The mixed powder can be obtained by ball milling or any other method that can mix the powder evenly.
[0025] Furthermore, the temperature of the dehydrogenation high temperature consolidation treatment in step S8 is 900-1300°C, the heating rate is 10-200°C / min, the holding time is 0.5-4h, and the vacuum degree is 5×10 -3 The sintering process includes one of vacuum hot pressing sintering, spark ion beam sintering and hot isostatic pressing sintering.
[0026] The gradient titanium-based composite material of the multi-level network structure composite laminate prepared by the above-mentioned preparation method of the present invention also belongs to the protection scope of the present invention.
[0027] The customized construction method of the high-strength and toughness titanium-based composite material bimodal structure of the present invention is guided by improving the strength and toughness matching, and the coarse grain area and fine grain area are customized to show the bimodal structural characteristics. By adjusting the grain size in the raw material powder, the powders of different grain sizes are accurately assembled, and the ratio, distribution and content of coarse / fine grains are controlled, and then the bulk material is formed through high-temperature consolidation. The obtained titanium-based composite material shows customized bimodal structural characteristics, and the strength is greatly improved without reducing the plasticity.
[0028] The bimodal grain distribution in the present invention is firstly controlled by regulating the particle size and ratio of powders A and B to preliminarily control the grain size of coarse crystals and fine crystals, and then by controlling the high temperature consolidation parameters (sintering temperature, heating rate, and holding time), the final crystal region size is controlled. Within the preferred preparation parameter range of the present invention, the smaller the powder particle size of powders A and B, the higher the volume fraction of the reinforcement, the lower the sintering temperature, the faster the heating rate, and the shorter the holding time, the smaller the crystal region size. For example, if the fine crystal region size of the TC4-based composite material is controlled to be 6 to 8 μm and the coarse crystal region is 11 to 14 μm, the particle size of powder A should be selected to be <150 μm, the particle size of powder B should be selected to be 25 to 120 μm, the volume fraction of the reinforcement should be selected to be 2.5% to 4%, and the sintering temperature should be 1100 to 1200 ° C.
[0029] Compared with the prior art, the present invention has the following advantages and effects:
[0030] (1) According to the customized construction method of the bimodal structure of the high-strength and toughness titanium-based composite material provided by the present invention, the volume fraction of the raw material powder reinforcement and the high-temperature consolidation process parameters are designed and controlled to achieve customized control of the grain size and distribution of the bimodal structure titanium-based composite material. Generally, the higher the volume fraction of the reinforcement and the lower the consolidation temperature, the more obvious the fine grain effect, thereby achieving the strength and toughness goals of the titanium-based composite material.
[0031] (2) The titanium-based composite material obtained by the present invention has a microstructure consisting of two regions: a coarse-grained region and a fine-grained region. The fine-grained region is composed of a titanium-based composite material with a reinforcement content of 1 to 20 vol.%, and micro / nano multi-component reinforcements are evenly dispersed inside the region. The grain size of the entire fine-grained region is in the range of 3 to 8 μm, while the coarse-grained region is a matrix titanium alloy with a grain size in the range of 10 to 100 μm.
[0032] (3) Based on the above structural characteristics, the bulk titanium-based composite material obtained by the present invention exhibits high strength and good plasticity. While maintaining the same plasticity as the matrix alloy, its strength is increased by 20% to 35% compared with the matrix alloy. The bulk material has not undergone any secondary plastic deformation, and its performance is equivalent to that of the matrix alloy forgings. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0034] Figure 1 This is a flow chart of the titanium-based composite material prepared by the present invention;
[0035] Figure 2 This is a scanning electron microscope image of the (TiB+TiC) / TC4 composite material powder used in Example 1;
[0036] Figure 3 Schematic diagram of the microstructure of the titanium-based composite material in Examples 1 to 3;
[0037] Figure 4 1 is the room temperature tensile stress-strain curve of the titanium-based composite materials in Examples 1 to 5 and TC4. DETAILED DESCRIPTION
[0038] The following examples will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. For those skilled in the art, several changes and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. The present invention is described in detail below in conjunction with specific embodiments:
[0039] The present invention provides a high-strength and tough titanium-based composite material with a bimodal structure, comprising the following steps:
[0040] S1: To improve the matching of strength and plasticity, the grain size of the coarse-grained area and the fine-grained area is customized;
[0041] S2: According to the customized design requirements of the grain size of the coarse / fine grain area, the powder type and the content of the reinforcing phase are adjusted. Among them, the fine grain area uses titanium-based composite material powder (denoted as A), and the type and content of its matrix (denoted as A1) and reinforcement (denoted as A2) are adjusted; the coarse grain area uses titanium alloy powder (denoted as B), and its powder type and particle size are adjusted;
[0042] S3: Prepare titanium-based composite material powder selected for fine-grained area. First, according to the design of S2, the matrix A1 and the reinforcement or the additive for generating the reinforcement A2 are pressed to form an electrode rod, and a titanium-based composite material intermediate ingot with uniform composition and standard composite electrode size is prepared by vacuum consumable melting or induction melting technology, and processed into the electrode rod required for powder making, and finally the rod is subjected to electrode induction melting gas atomization powder making, that is, the titanium-based composite material powder A with the reinforcement content meeting the expected is obtained;
[0043] S4: According to the design of S2, the powder A obtained in S3 is screened to obtain powders A with different particle sizes;
[0044] S5: According to the design of S2, the matrix titanium alloy powder B is screened to obtain powders B with different particle sizes;
[0045] S6: Drying the powder A and powder B obtained in S4 and S5 respectively;
[0046] S7: Mix the two powders obtained in S6 evenly according to the ratio designed in S2;
[0047] S8: The mixed powder obtained in S7 is placed in a sintering furnace for dehydrogenation and high-temperature consolidation to obtain a bimodal structured high-strength and tough titanium-based composite material block with different grain sizes.
[0048] Evaluation criteria and methods
[0049] 1. Powder structure morphology: TiB and TiC are distributed in a network structure inside, realizing the pre-implantation of reinforcements; the composite material structure after high-temperature consolidation shows an obvious bimodal structure, in which the fine-grained area presents a uniform equiaxed structure, and micro-nano multi-reinforcements are evenly distributed inside;
[0050] The test method is: set 5kV voltage on TASCAN RISE-MAGNA to observe the microstructure.
[0051] 2. Tensile performance test-tensile strength and elongation;
[0052] The test method is: the mechanical properties test is carried out on a Zwick Z20 universal testing machine, the sample is a sheet tensile sample, and the elongation is measured using an extensometer.
[0053] Example 1
[0054] (1) In order to achieve room temperature yield strength of TC4-based composite materials higher than 900 MPa, tensile strength higher than 1000 MPa, and elongation higher than 7%, the fine grain size range of the bimodal structure is designed to be 7.5-8 μm, and the coarse grain size range is 11-12 μm.
[0055] (2) Sponge titanium, pure aluminum wire, aluminum-vanadium alloy, and boron carbide powder are used as raw materials, wherein the alloy matrix is weighed according to the ratio of Ti-6A1-4V and mechanically pressed into a consumable electrode; the electrode is placed in a vacuum consumable arc furnace for vacuum melting twice, and the melting current is controlled to be 1.5 kA and the vacuum degree is 1×10 -3 Pa, to obtain a secondary ingot; the obtained secondary ingot is forged and stretched at 1000°C to obtain a rough billet, which is then machined and polished into a regular round rod; an electrode induction melting gas atomization powder making equipment is used to prepare a 5 vol.% (TiB+TiC) / TC4 composite material powder.
[0056] (3) The powder obtained in (2) is vibrated and sieved to select powder with a particle size of 120 to 150 μm.
[0057] (4) According to the grain size of the coarse grain zone, TC4 powder is selected as the matrix alloy, and its particle size ranges from 25 to 53 μm.
[0058] (5) The powders obtained in (3) and (4) are placed in a vacuum drying oven for drying.
[0059] (6) The two powders in step (5) are mixed uniformly in a ratio of 1:1 by a planetary ball mill at a rotation speed of 200 r / min for 4 h.
[0060] (7) The powder mixed in step (6) is placed in a vacuum sintering furnace to complete dehydrogenation sintering treatment, the high temperature consolidation temperature is 1100°C, the heating rate is 10°C / min, the holding time is 4h, the cooling method is furnace cooling, and the vacuum degree is 5×10 - 3 Pa.
[0061] Figure 1 The flow chart of the titanium-based composite material prepared by the present invention. The microstructure was observed by setting a voltage of 5 kV on TASCAN RISE-MAGNA. Figure 2 This is the scanning electron microscope image of the (TiB+TiC) / TC4 composite material powder. The material has a uniform equiaxed structure. Figure 3The titanium-based composite material with a bimodal structure obtained in Example 1 has a structure characterized by a continuous coarse-grained region surrounding a fine-grained region, an average coarse-grained grain size of 11.85 μm, an average fine-grained grain size of 7.79 μm, micro-nano TiB and TiC nucleate at grain boundaries and in grains to form a fine-grained region, Figure 4 The experimental results show that the room temperature yield strength of the titanium-based composite material prepared in this embodiment is 933.19 MPa, the tensile strength is 1060.33 MPa, and the elongation after fracture is 8.33%. Compared with the base alloy prepared by the same process, the strength is increased by 210 MPa without losing plasticity.
[0062] Example 2
[0063] (1) In order to achieve room temperature yield strength of TC4-based composite materials higher than 900 MPa, tensile strength higher than 1000 MPa, and elongation higher than 7%, the fine grain size range of the bimodal structure is designed to be 7.5-8 μm, and the coarse grain size range is 13-14 μm.
[0064] (2) Sponge titanium, pure aluminum wire, aluminum-vanadium alloy, and boron carbide powder are used as raw materials, wherein the alloy matrix is weighed according to the ratio of Ti-6A1-4V and mechanically pressed into a consumable electrode; the electrode is placed in a vacuum consumable arc furnace for vacuum melting twice, and the melting current is controlled to be 1.5 kA and the vacuum degree is 1×10 -3 Pa, to obtain a secondary ingot; the obtained secondary ingot is forged and stretched at 1000°C to obtain a rough billet, which is then machined and polished into a regular round rod; an electrode induction melting gas atomization powder making equipment is used to prepare a 5 vol.% (TiB+TiC) / TC4 composite material powder.
[0065] (3) The powder obtained in (2) is vibrated and sieved to select powder with a particle size of 120 to 150 μm.
[0066] (4) According to the grain size of the coarse grain zone, TC4 powder is selected as the matrix alloy powder, and its particle size range is 96 to 120 μm.
[0067] (5) The powder obtained in (3) and (4) is placed in a vacuum drying oven for drying.
[0068] (6) The two powders in step (5) were mixed uniformly in a ratio of 1:1 by a planetary ball mill at a rotation speed of 200 r / min and a ball milling time of 4 h.
[0069] (7) The powder mixed in step (6) is placed in a vacuum sintering furnace to complete dehydrogenation sintering treatment. The sintering temperature is 1100°C, the heating rate is 10°C / min, the holding time is 4h, the cooling method is furnace cooling, and the vacuum degree is 5×10 -3 Pa.
[0070] The microstructure was observed by setting the voltage of 5kV on TASCAN RISE-MAGNA. Figure 3 The titanium-based composite material with a bimodal structure obtained in Example 2 has similar organizational characteristics to those in Example 1, with an average coarse grain size of 13.30 μm and an average fine grain size of 7.84 μm. Figure 4 The results of the tensile properties test show that the titanium-based composite material prepared in this embodiment has a room temperature yield strength of 943.17 MPa, a tensile strength of 1036.24 MPa, and an elongation after fracture of 9.48%. Compared with the base alloy prepared by the same process, the strength is increased by 186 MPa without losing plasticity.
[0071] Example 3
[0072] (1) In order to achieve room temperature yield strength of TC4-based composite materials higher than 900 MPa, tensile strength higher than 1000 MPa, and elongation higher than 7%, the fine grain size range of the bimodal structure is designed to be 7-7.5 μm, and the coarse grain size range is 11-12 μm.
[0073] (2) Sponge titanium, pure aluminum wire, aluminum-vanadium alloy, and boron carbide powder are used as raw materials, wherein the alloy matrix is weighed according to the ratio of Ti-6A1-4V and mechanically pressed into a consumable electrode; the electrode is placed in a vacuum consumable arc furnace for vacuum melting twice, and the melting current is controlled to be 1.5 kA and the vacuum degree is 1×10 -3 Pa, to obtain a secondary ingot; the obtained secondary ingot is forged and stretched at 1000°C to obtain a rough billet, which is then machined and polished into a regular round rod; an electrode induction melting gas atomization powder making equipment is used to prepare a 5 vol.% (TiB+TiC) / TC4 composite material powder.
[0074] (3) The powder obtained in (2) is vibrated and sieved to select powder with a particle size of 120 to 150 μm. (4) According to the grain size of the coarse grain area, TC4 powder is selected as the base alloy powder, and its particle size range is 25 to 53 μm.
[0075] (5) The powder obtained in (3) and (4) is placed in a vacuum drying oven for drying.
[0076] (6) The mixed powder in step (5) is mixed uniformly in a planetary ball mill at a ratio of A:B of 4:1, with a rotation speed of 200 r / min and a ball milling time of 4 h.
[0077] (7) The mixed powder in step (6) is placed in a vacuum sintering furnace to complete dehydrogenation sintering treatment. The sintering temperature is 1100°C, the heating rate is 10°C / min, the holding time is 4h, the cooling method is furnace cooling, and the vacuum degree is 5×10-3 Pa.
[0078] The microstructure was observed by setting the voltage of 5kV on TASCAN RISE-MAGNA. Figure 3 The titanium-based composite material with a bimodal structure obtained in Example 3 has organizational characteristics in which the fine-grained area expands, connects, overlaps and gradually surrounds the coarse-grained area, and micro-nano reinforcements are precipitated at the boundaries of the fine-grained area and at the grain boundaries and inside of the grains. The average coarse-grained grain size is 11.51 μm, and the average fine-grained grain size is 7.08 μm. Figure 4 The results of the tensile properties test show that the titanium-based composite material prepared in this embodiment has a room temperature yield strength of 1009.75 MPa, a tensile strength of 1121.72 MPa, and an elongation after fracture of 8.27%. Compared with the base alloy prepared by the same process, the tensile strength is increased by 270 MPa without losing plasticity.
[0079] Example 4
[0080] (1) In order to achieve room temperature yield strength of TC4-based composite materials higher than 900 MPa, tensile strength higher than 1000 MPa, and elongation higher than 7%, the fine grain size range of the bimodal structure is designed to be 7.5-8 μm, and the coarse grain size range is 13-14 μm.
[0081] (2) Sponge titanium, pure aluminum wire, aluminum-vanadium alloy, and boron carbide powder are used as raw materials, wherein the alloy matrix is weighed according to the ratio of Ti-6A1-4V and mechanically pressed into a consumable electrode; the electrode is placed in a vacuum consumable arc furnace for vacuum melting twice, and the melting current is controlled to be 1.5 kA and the vacuum degree is 1×10 -3 Pa, to obtain a secondary ingot; the obtained secondary ingot is forged and stretched at 1000°C to obtain a rough billet, which is then machined and polished into a regular round rod; an electrode induction melting gas atomization powder making equipment is used to prepare a 4 vol.% (TiB+TiC) / TC4 composite material powder.
[0082] (3) The powder obtained in (2) is vibrated and sieved to select powder with a particle size of 120 to 150 μm. (4) According to the grain size of the coarse grain area, TC4 powder is selected as the base alloy powder, and its particle size range is 25 to 53 μm.
[0083] (5) The powder obtained in (3) and (4) is placed in a vacuum drying oven for drying.
[0084] (6) The mixed powder in step (5) is mixed uniformly in a planetary ball mill at a ratio of A:B of 1:1, with a rotation speed of 200 r / min and a ball milling time of 4 h.
[0085] (7) The powder mixed in step (6) is placed in a vacuum sintering furnace to complete dehydrogenation sintering treatment. The sintering temperature is 1200°C, the heating rate is 10°C / min, the holding time is 4h, the cooling method is furnace cooling, and the vacuum degree is 5×10 -3 Pa.
[0086] The titanium-based composite material obtained in this embodiment has an average coarse grain size of 13.3 μm and an average fine grain size of 7.61 μm. Figure 4 The experimental results show that the room temperature yield strength is 971.67MPa, the tensile strength is 1049.21MPa, and the elongation after fracture is 7.4%. Compared with the base alloy prepared by the same process, the tensile strength is increased by 200MPa without losing plasticity.
[0087] Example 5
[0088] (1) In order to achieve room temperature yield strength of TC4-based composite materials higher than 900 MPa, tensile strength higher than 1000 MPa, and elongation higher than 7%, the fine grain size range of the bimodal structure is designed to be 7-7.5 μm, and the coarse grain size range is 13-14 μm.
[0089] (2) Sponge titanium, pure aluminum wire, aluminum-vanadium alloy, and boron carbide powder are used as raw materials, wherein the alloy matrix is weighed according to the ratio of Ti-6A1-4V and mechanically pressed into a consumable electrode; the electrode is placed in a vacuum consumable arc furnace for vacuum melting twice, and the melting current is controlled to be 1.5 kA and the vacuum degree is 1×10 -3 Pa, to obtain a secondary ingot; the obtained secondary ingot is forged and stretched at 1000°C to obtain a rough billet, which is then machined and polished into a regular round rod; an electrode induction melting gas atomization powder making equipment is used to prepare a 4 vol.% (TiB+TiC) / TC4 composite material powder.
[0090] (3) The powder obtained in (2) is vibrated and sieved to select powder with a particle size of 75 to 96 μm.
[0091] (4) According to the grain size of the coarse grain zone, TC4 powder is selected as the matrix alloy powder, and its particle size range is 96 to 120 μm.
[0092] (5) The powder obtained in (3) and (4) is placed in a vacuum drying oven for drying.
[0093] (6) The mixed powder in step (5) was mixed uniformly in a planetary ball mill at a ratio of A:B of 3:1, with a rotation speed of 200 r / min and a ball milling time of 4 h.
[0094] (7) The powder mixed in step (6) is placed in a vacuum sintering furnace to complete dehydrogenation sintering treatment. The sintering temperature is 1200°C, the heating rate is 10°C / min, the holding time is 4h, the cooling method is furnace cooling, and the vacuum degree is 5×10 -3 Pa.
[0095] The titanium-based composite material obtained in this embodiment has an average coarse grain size of 13.45 μm and an average fine grain size of 7.14 μm. Figure 4 The results of the tensile properties test show that the titanium-based composite material prepared in this embodiment has a room temperature yield strength of 997.45 MPa, a tensile strength of 1119.33 MPa, and an elongation after fracture of 7.77%. Compared with the base alloy prepared by the same process, the tensile strength is increased by 270 MPa without losing plasticity.
[0096] Example 6
[0097] (1) In order to achieve room temperature yield strength of IMI834-based composite materials higher than 1000 MPa, tensile strength higher than 1150 MPa, and elongation higher than 4%, the fine grain size range of the bimodal structure is designed to be 7-9 μm, and the coarse grain size range is 13-15 μm.
[0098] (2) Sponge titanium, pure aluminum wire, aluminum-niobium alloy, aluminum-molybdenum alloy, titanium-tin alloy, silicon, carbon powder, zirconium, and lanthanum hexaboride powder were used as raw materials and mechanically pressed into consumable electrodes; the electrodes were placed in a vacuum consumable arc furnace for vacuum melting twice, with the melting current controlled to 2 kA and the vacuum degree to 1 × 10 -3 Pa, to obtain a secondary ingot; the obtained secondary ingot is forged and stretched at 1200°C to obtain a rough billet, which is then machined and polished into a regular round rod; an electrode induction melting gas atomization powder making equipment is used to prepare a 2.4 vol.% (TiB+La2O3) / IMI834 composite material powder.
[0099] (3) The powder obtained in (2) is vibrated and sieved to select powder with a particle size of 25 to 53 μm.
[0100] (4) According to the grain size of the coarse grain area, the matrix alloy powder is selected as IMI834 powder, and its particle size range is 120 to 150 μm.
[0101] (5) The powder obtained in (3) and (4) is placed in a vacuum drying oven for drying.
[0102] (6) The mixed powder in step (5) is mixed uniformly in a planetary ball mill at a ratio of A:B of 1:1, with a rotation speed of 200 r / min and a ball milling time of 5 h.
[0103] (7) The powder mixed in step (6) is placed in a vacuum sintering furnace to complete dehydrogenation sintering treatment. The sintering temperature is 1100°C, the heating rate is 10°C / min, the holding time is 4h, the cooling method is furnace cooling, and the vacuum degree is 5×10 -3 Pa.
[0104] (8) Tensile property test results: The experimental results show that the room temperature yield strength of the titanium-based composite material prepared in this embodiment is 1010 MPa, the tensile strength is 1160 MPa, and the elongation after fracture is 5.8%.
[0105] Comparative Example 1
[0106] This comparative example is a comparative example of Example 1.
[0107] This comparative example provides a method for preparing a titanium-based composite material with a homogeneous structure. In this comparative example, the other steps are basically the same as those in Example 1, except that: no customized design of a bimodal configuration is performed for the target performance of the titanium-based composite material, but only by mixing TiB2, B4C, and B powder reinforcement reactants with spherical TC4 powder to keep the reinforcement type (TiB+TiC) and volume fraction (2.5%) the same, the titanium-based composite material prepared in Comparative Example 1 has the following characteristics compared with Example 1: (1) There is no bimodal structure in the organization, but a homogeneous structure, and the reinforcement is micron-sized, with low dispersion and low strength and toughness matching. (2) The tensile strength of the titanium-based composite material prepared in Comparative Example 1 is 1010.2MPa, and the elongation after fracture is 1.8%. Compared with Example 1, the comprehensive performance is significantly different.
[0108] Comparative Example 2
[0109] This comparative example is a comparative example of Example 2.
[0110] This comparative example provides a method for preparing a titanium-based composite material with a bimodal structure. In this comparative example, the other steps are basically the same as those in Example 2, except that the sintering temperature of step (7) is 850°C. The titanium-based composite material prepared in Comparative Example 2 has the following characteristics compared with Example 2: the material has a low density, a large number of micropores exist in the microstructure, the material exhibits obvious room temperature brittleness, and the elongation is only 2.3%, which is much lower than that in Example 2. Therefore, the preferred preparation parameters of the invention are an important basis for material organization regulation and comprehensive performance improvement.
[0111] Generally speaking, when the grain size of the fine grain zone is close, the larger the grain size of the coarse grain zone, the better the plasticity of the material, refer to Example 1 and Example 2; when the size of the coarse and fine grain zones is close, the smaller the grain size of the fine grain zone, the higher the material strength, refer to Example 1 and Example 3.
[0112] The implementation methods of the present invention are not limited to the above-mentioned embodiments, and any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A customized method for constructing a bimodal structure of a high-strength and high-toughness titanium-based composite material, characterized in that: The specific preparation steps are as follows: S1. To improve the matching of strength and plasticity, the grain size of the coarse-grained area and the fine-grained area is customized according to the performance target of high-strength and toughness titanium-based composite materials; S2. According to the customized design requirements of the grain size of the coarse / fine grain area, the type of powder and the content of the reinforcing phase are adjusted; wherein, the fine grain area uses titanium-based composite material powder A, which includes matrix alloy A1 and reinforcement A2, and the type and particle size of A are adjusted. The type of A is specifically to adjust the type and content of A1 and A2; the coarse grain area uses titanium alloy powder B, and the type and particle size of powder B are adjusted; S3, according to the type and content of A2 designed in S2, prepare titanium-based composite material powder A selected for fine grain region; the preparation method of titanium-based composite material powder A is one of rotating electrode method, water atomization method and gas atomization method; S4. According to the design of S2, the powder A obtained in S3 is screened to obtain powders A with different particle sizes; S5. According to the design of S2, the titanium alloy powder B is screened to obtain titanium alloy powders B with different particle sizes; S6, drying the titanium-based composite material powder A and the titanium alloy powder B obtained in S4 and S5 respectively; S7, mixing the two powders obtained in S6 evenly according to the ratio designed in S2 to obtain a mixed powder; S8, subjecting the mixed powder obtained in S7 to a dehydrogenation high-temperature consolidation treatment to obtain a high-strength and tough titanium-based composite material with a bimodal structure having different grain sizes; In step S2, the particle size range of the titanium-based composite material powder A includes one of 25-53 μm, 53-75 μm, 75-96 μm, 96-120 μm, 120-150 μm, 150-180 μm, 180-230 μm, and 230-250 μm; In step S2, the base alloy powder B includes pure titanium or titanium alloy, and the particle size range includes one of 25-53 μm, 53-75 μm, 75-96 μm, 96-120 μm, and 120-150 μm; In step S7, in the mixed powder of powder A and powder B, the volume fraction of the titanium-based composite material powder A is 10% to 90%.
2. The customized construction method according to claim 1, characterized in that: In step S1, the grain size of the fine-grained region is in the range of 3 to 8 μm, and the grain size of the coarse-grained region is in the range of 10 to 100 μm.
3. The customized construction method according to claim 1, characterized in that: In step S2, the matrix alloy A1 in the titanium-based composite material powder A includes one or more of pure titanium and titanium alloy, and the reinforcement A2 includes TiB, TiC, La2O3, Ti x Si y One or more of the reinforcements, Ti x Si y Where x=1~5, y=1~4.
4. The customized construction method according to claim 1, characterized in that: In step S2, the volume fraction of the reinforcement A2 in the titanium-based composite material powder A is 1-20%.
5. The customized construction method according to claim 1, characterized in that: In step S7, the mixing method includes ball milling, the equipment speed range is 100-400 r / min, the time is 0.5-12 h, and the ball-to-material ratio is 0:1-5:
1.
6. The customized construction method according to claim 1, characterized in that: In step S8, the temperature of the dehydrogenation high-temperature consolidation treatment is 900-1300°C, the heating rate is 10-200°C / min, and the insulation time is 0.5-4h.
7. A high-strength and toughness titanium-based composite material prepared by the customized construction method as described in any one of claims 1 to 6.
Citation Information
Patent Citations
Heterogeneous-structure titanium-based composite material and preparation method and application thereof
CN111961902A